Fight obesity via photographic images / Nor Fariza Baharuddin … [et al.] - Baharuddin, Nor Fariza; Nik Aziz, Nik Nor Azidah; Wan Mohd Zain, Wan Nor Ayuni; Abdul Samat, Raziq; Meor Hamzah, Meor Hasmadi (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Newspaper articles that quoted from the Berita Harian dated 18 April 2000, the practice of unhealthy lifestyle among the people of this country is the cause why Malaysia is categorized as a country that had higher obesity rates than other countries in the region. The contributors of obesity are overeating, high calorie foods and eating late at night. Malaysians are well known for their habit of eating late at night and most of the time they will spent enjoying a high-calorie food. Various preventive efforts has been taken by Ministry of Health, Malaysia. However, this problem still persists. Therefore, the purpose of this research is to help obese people to eat healthily. Two research methods are employed, the interview for the daily menu of the obese subjects and the questionnaire to identify the effectiveness of photographic poster in order to change the unhealthy eating habits among them. As a result, the researcher found that the poster has changed obese people's thought in adopting a healthy diet compared to their previous dietary habits.